Vascular endothelial function and oxidation stress in patients with Behçet's disease - Chambers,JC; Haskard,DO; Kooner,JS (Heart, 2000)
Background: Behçet's disease is a multisystem inflammatory disorder, commonly complicated by vascular thrombosis and arterial aneurysm formation. We have tested the hypothesis that vascular endothelial function is impaired in Behçet's disease, and may reflect increased levels of oxidation stress. Methods: We investigated 19 patients with Behçet's disease (aged 18-50 years, 9 male) and 21 healthy volunteers (aged 18-50 years, 10 male). Brachial artery flow-mediated dilatation (endothelium dependent), and glyceryltrinitrate induced dilatation (GTN, endothelium independent), were measured using high resolution ultrasound. To investigate the role of oxidant stress mechanisms, vascular measurements were repeated 1 hour after administration of vitamin C (1g IV) in 12 patients, and 12 controls. Results: Flow-mediated dilatation was reduced in patients compared to controls (0.7±0.9 vs 5.7±0.9 %, p=0.001). In contrast, there were no significant differences in brachial arterial diameter between patients and controls (4.2±0.2 vs 4.0±0.2 mm, p=0.47) or in brachial artery dilatation in response to sublingual GTN (19.7±1.9 vs 19.7±1.2 %, p=0.98). Administration of vitamin C increased flow-mediated dilatation in patients with Behçet's disease (0.2±0.7 to 3.5±1.0 %, p=0.002), but not in controls (4.3±0.6 to 4.7±0.4%, p=0.51). GTN induced dilatation and brachial arterial diameter were unchanged after vitamin C in both groups. Conclusions: Vascular endothelial function is impaired in Behçet's disease, is mediated by oxidant stress, and can be reversed rapidly by vitamin C. Our results provide new insights in mechanisms underlying Behçet's disease, and provide a rationale for therapeutic studies aimed at reducing vascular complication in this disorder.